2020
DOI: 10.1101/2020.08.31.275701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A COVID-19 vaccine candidate using SpyCatcher multimerization of the SARS-CoV-2 spike protein receptor-binding domain induces potent neutralising antibody responses

Abstract: There is dire need for an effective and affordable vaccine against SARS-CoV-2 to tackle the ongoing pandemic. In this study, we describe a modular virus-like particle vaccine candidate displaying the SARS-CoV-2 spike glycoprotein receptor-binding domain (RBD) using SpyTag/SpyCatcher technology (RBD-SpyVLP). Low doses of RBD-SpyVLP in a prime-boost regimen induced a strong neutralising antibody response in mice and pigs that was superior to convalescent human sera. We evaluated antibody quality using ACE2 block… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 64 publications
4
46
1
1
Order By: Relevance
“…In conclusion, we confirmed that multimerization of RBDs on nanoparticles enhances immunogenicity compared with soluble antigen ( 33 , 48 ) and further showed that homotypic SARS-2 nanoparticle immunization produced IgG responses that bound zoonotic RBDs and neutralized heterologous coronaviruses after boosting. By contrast, soluble SARS-2 S immunization and natural infection with SARS-CoV-2 resulted in weak or no heterologous responses in plasmas.…”
Section: Main Textsupporting
confidence: 74%
See 2 more Smart Citations
“…In conclusion, we confirmed that multimerization of RBDs on nanoparticles enhances immunogenicity compared with soluble antigen ( 33 , 48 ) and further showed that homotypic SARS-2 nanoparticle immunization produced IgG responses that bound zoonotic RBDs and neutralized heterologous coronaviruses after boosting. By contrast, soluble SARS-2 S immunization and natural infection with SARS-CoV-2 resulted in weak or no heterologous responses in plasmas.…”
Section: Main Textsupporting
confidence: 74%
“…In one such approach, multiple copies of an engineered protein domain called SpyCatcher fused to subunits of a virus-like particle form spontaneous isopeptide bonds to purified antigens tagged with a 13-residue SpyTag ( 2932 ). The SpyCatcher-SpyTag system was used to prepare multimerized SARS-CoV-2 RBD or S trimer that elicited high titers of neutralizing antibodies ( 33 , 34 ). Although promising for protection against SARS-CoV-2, coronavirus reservoirs in bats suggest future cross-species transmission ( 6, 7, 35 ), necessitating a vaccine that protects against emerging coronaviruses as well as SARS-CoV-2.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The already high Ace2 competition titers elicited after two immunizations were significantly boosted after a third immunization ( Figure 6, Supplementary Figure 4F, 6E, 7D). In contrast to recently described, highly immunogenic multi-component nanoparticle systems (37,38), the present single component, trimeric RBD might be easier to purify and manufacture and in humans should elicit a higher proportion of RBD directed antibodies because of its host derived trimerization sequence. In summary, the present study describes the design of a disulfide linked trimeric immunogen that is stable to long term thermal stress and induces robust neutralizing antibodies against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 77%
“…Monomeric versions of immunogens elicit lower binding and neutralizing antibodies than multimeric version (29,35,38,41). Potential strategies to improve neutralizing antibody titers include fusion protein containing repetitive antigenic proteins, Fc fusion based dimerization, nanoparticle design and display strategies, and VLP based display platforms (36)(37)(38)(39)(40)(41)(42)(43). While effective, several display strategies lead to significant antibody titers against the display scaffold or oligomerization motif, such antibodies might either show undesirable side effects in a small fraction of individuals or direct the response away from the intended target after repeated immunizations.…”
Section: Introductionmentioning
confidence: 99%